2020
DOI: 10.3906/bot-1902-15
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of antioxidant activity in maize (Zeamays L.) by exogenous application of sulfur under saline conditions

Abstract: One of the major effects of salt stress is high production of reactive oxygen species that adversely affect essential cellular metabolic pathways. To limit the elevated production of reactive oxygen species, plants stimulate various types of antioxidants. In this study, sulfur was used to induce tolerance against oxidative stress through modulation of the activities of various antioxidants. Two maize genotypes (Agatti 2003 and Pak Afgoi 2003) were subjected to different salinity (25 and 75 mM) and sulfur (40 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…SOD plays a vital role in the scavenging of superoxide radicals [48]. Previously, several workers have reported that the activity of SOD increases significantly in plants as a result of various stresses, especially water stress [52][53][54][55]. In our work, an overall increase in SOD activity was recorded under sorbitol, mannitol, sucrose, or PEG-induced water deficit.…”
Section: Discussionsupporting
confidence: 61%
“…SOD plays a vital role in the scavenging of superoxide radicals [48]. Previously, several workers have reported that the activity of SOD increases significantly in plants as a result of various stresses, especially water stress [52][53][54][55]. In our work, an overall increase in SOD activity was recorded under sorbitol, mannitol, sucrose, or PEG-induced water deficit.…”
Section: Discussionsupporting
confidence: 61%
“…Increasing the MDA content of algae due to exposure of heavy metal has been previously proven by many researchers (Piotrowska-Niczyporuk et al, 2012;Rai et al, 2013;Çelekli et al, 2016). In addition, salinity gradients increased MDA content in Polygonum equisetiforme (Boughalleb et al, 2020) and Zea mays (Rıffat and Ahmad, 2020). The consequent formation of MDA is a breakdown product of membrane lipid peroxidation when insufficient detoxification of ROS by biota occurs (Pinto et al, 2003).…”
Section: Resultsmentioning
confidence: 88%
“…Study of the effect of salinity on tomato ( Parvin et al, 2019 ) showed a strong increase of SOD, APX, GPX, and DHAR activity proportionally to NaCl concentration during salt stress. Riffat & Ahmad (2020) showed for Zea mays L. that under salt-stress treatment, amounts of ascorbate and tocopherols decreased and production of SOD, CAT, POX, and some compounds (i.e., phenolics, carotenoids, MDA) increased. The authors emphasized the role of exogenous sulfur as an inductor of salt tolerance because of enhancement of SOD, POX, CAT, increasing of AsA, tocopherol, phenolics, and decreasing carotenoids and MDA during sulfur supply.…”
Section: Survey Methodologymentioning
confidence: 99%